The nation brand of Spain on the internet through the “I need Spain” campaign - Corbacho Valencia, Juan Manuel; Valderrama Santomé, Mónica; García Mirón, Silvia (Historia y Comunicación Social, 2014)
Both commercial and nation brands get differentiated by perceived and broadcasted associations and perceptions that are measureable through different reports. This paper focusses on the last campaign to foster Spain’s nation brand between different target audiences, mainly from abroad. The campaign titled “I need Spain” has run through digital media and different platforms. The authors analyze the role played by the agents involved and future perspectives on this issue.
Keywords: Nation brand; internationalisation; brand management; digital media.